The Implementation of Blended Learning Using Google Application in Mathematics Learning in the Pandemic Period - Nurul Kustiyati; Dewi Nur Cahyaningsih (Teknodika, 2021)
This study was aimed to enhance the learning innovation during pandemic so that it could still increse the activeness of learning mathematic even though the teacher and the student rarely face to face. The design of this study was classroom action research with four stages, as follows: planning, acting, observing, and reflecting. These stages was done in two cycles since the percentage of students’ activeness in the second cycle has achieved the predetermined succes indicator which was >80%. Each cycle focused on the rule of sine and cosine materials. This study was done in Al Azhar Syifa Budi Solo Senior High School. In this study, the researcher acted as the subject of the class action, while the students of X MIPA Tahfidz as the subject of the class action recipient. The data analysis was done in descriptive way. Based on the observation before the action done, the percentage of students’ activeness was 45,8%. In the first cycle, the percentage improved 17% which was 62,8%. In the second cycle, the percentage improve again to 83,34% (has achieved the succes indicators). According to the result of this study, it can be concluded the implementation of blended learning by using google application can improve the students’ activeness in mathematic learning during pandemic